Minor contribution of mutations at iniA codon 501 and embC-embA intergenic region in ethambutol-resistant clinical Mycobacterium tuberculosis isolates in Kuwait - Ahmad Suhail; Jaber Al-Anoud; Mokaddas Eiman (BMC, 2009)
Abstract Background Ethambutol (EMB) is a first-line drug for the treatment of tuberculosis (TB). Resistance to EMB in Mycobacterium tuberculosis isolates is mediated by mutations in several genes involved in arabinan synthesis notably three emb (arabinosyl transferase) and iniA (isoniazid-inducible) genes. Most epidemiologically unrelated EMB-resistant M. tuberculosis strains contain mutations at embB codons 306, 406 and 497, embC-embA intergenic region (IGR) and iniA codon 501 (iniA501). Objective To develop a more comprehensive molecular screen for EMB-resistance detectioamong epidemiologically unrelated EMB-resistant M. tuberculosis strains previously analyzed for embB codon 306, 406 and 497 mutations by including analysis of mutations at iniA501 and in embC-embA IGR. Methods Fifty consecutive and phenotypically documented EMB-resistant and 25 pansusceptible M. tuberculosis strains isolated from 75 different TB patients over a four-year period in Kuwait were analyzed. Mutations at iniA501 were detected by PCR amplification followed by restriction fragment length polymorphism (RFLP) patterns generated with Hpy 99 I. Direct DNA sequencing was used to confirm RFLP results and for detecting mutations in embC-embA IGR. Results Nearly same number of EMB-resistant M. tuberculosis strains were resistant to EMB alone and EMB together with additional resistance to rifampicin and isoniazid (9 of 50, 18% and 11 of 50, 22%, respectively). All the 25 pansusceptible strains contained wild-type sequences at iniA501 and in embC-embA IGR. The analysis of 50 EMB-resistant M. tuberculosis isolates showed that only one strain contained a mutated iniA501 while no mutation was detected in embC-embA IGR in any of the isolate. Conclusion Analysis of iniA501 and embC-embA IGR in epidemiologically unrelated EMB-resistant M. tuberculosis isolates in Kuwait indicate that mutations at these locations occur very infrequently and their inclusion for the development of a comprehensive molecular screen will make only minor contribution towards rapid EMB resistance detection.